UPAYA MENINGKATKAN KEMAMPUAN MENULIS TEKS REKON MELALUI PENDEKATANTEACHING AT THE RIGHT LEVEL DENGAN MEDIA INTERAKTIF (PENELITIAN TINDAKAN KELAS PADA SISWA KELAS X² DI SMA LABORATORIUMPERCONTOHAN UNIVERSITAS PENDIDIKAN INDONESIA) - Syarifah Pertiwi (CV. ADIBA AISHA AMIRA, 2025)
Learning Indonesian language is closely related to language skills including; listening, speaking, reading and writing. An Indonesian language education teacher is expected to be able to teach and train students in their mastery of language skills that are useful in social life. The purpose of this study is to improve the ability and skills of writing recon texts in class X². This Classroom Action Research focuses on efforts to improve the ability to write recon texts through the Teaching at the Right Level approach, recon texts are texts that make an experience, either one's own experience or that of others by paying attention to the systematic writing in recon texts and understanding the types of recon texts including; factual recon texts, inspirational recon texts, and imaginative recon texts. Efforts to improve students' writing skills aim to achieve learning outcomes in writing elements through an attitude assessment process including independence, mutual cooperation, and critical reasoning in accordance with the Pancasila Student Profile in the Merdeka Curriculum. The target subjects of the study were class X² in the even semester of the 2023/2024 academic year. This research method with research design is Collaborative Classroom Action Research and Qualitative Descriptive, data collection techniques are observation, interviews, and document studies. The results of this study show an increase in the ability to write recon text successfully through the Teaching at the Right Level approach with interactive media from cycle I with a result of 82.19 and cycle II with a result of 84.09.